2009
DOI: 10.1021/la901239v
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation at the Surface of Poly(ethylene oxide)-Containing Biodegradable Poly(l-lactic acid) Blends

Abstract: The surface chemistry and in-depth distribution of the composition of a poly(ethylene oxide) (PEO)-containing biodegradable poly(l-lactic acid) (PLLA) blend matrix system have been investigated using X-ray photoelectron spectroscopy (XPS). This study reports detailed quantitative compositional information using a novel numerical method for determining depth profiles. The PEO system studied is an amphiphilic Pluronic P104 surfactant, PEO–b-poly(propylene oxide) (PPO)–b-PEO. The extent of phase separation is ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The calculated mesh sizes are of the same order of magnitude as the reported diameter of SDF-1α protein [4.4 nm (Huang, Shen et al 2003)]. Aside from the mesh size imposed on SDF-1α diffusion, hydrophilic and hydrophobic interactions with PEG and PLA domains, respectively, phase separation of the PLA and PEG domains (Yu, M. et al 2009), and inhomogeneity in the crosslinked network [i.e., microgel formation (Chi, Cai et al 2009)] can affect the release kinetics of SDF-1α from the PLEOF hydrogels.…”
Section: Discussionmentioning
confidence: 80%
“…The calculated mesh sizes are of the same order of magnitude as the reported diameter of SDF-1α protein [4.4 nm (Huang, Shen et al 2003)]. Aside from the mesh size imposed on SDF-1α diffusion, hydrophilic and hydrophobic interactions with PEG and PLA domains, respectively, phase separation of the PLA and PEG domains (Yu, M. et al 2009), and inhomogeneity in the crosslinked network [i.e., microgel formation (Chi, Cai et al 2009)] can affect the release kinetics of SDF-1α from the PLEOF hydrogels.…”
Section: Discussionmentioning
confidence: 80%
“…The occurrence of micropores can be interpreted as follow. Because of the phase separation in PLLA/PEO blend (it has been discussed in detail in ref and ) and the existence of strong shear field during spin-coating or blade-coating, phase-separated PEO-rich phases are interconnected with each other. , They play the role of pore-forming agent upon water etching, creating the interpenetrated microchannels in the membranes. The successful removal of PEO by water etching can be validated by both weight calculation and differential scanning calorimetry (DSC) results (Figure S2).…”
mentioning
confidence: 99%
“…In this study, we use poloxamer 188, which has an 1800 g/mol PPO midblock with a 3600 g/mol PEO block on each end. Poloxamers have been previously demonstrated to be miscible with PLA with a propensity to concentrate at the surface of PLA blends and impart wettability. Studies have shown that interaction of the PPO block is more favorable with PLA relative to the PEO segments. , This leads to the PPO block embedding in the PLA matrix and coating the surface with hydrophilic PEO. Additionally, poloxamer is ideal for our application, as it has been shown to be biodegradable …”
Section: Introductionmentioning
confidence: 99%